SYSTEMATIC LITERATURE REVIEW: STUDENT WORKSHEETS USING PROBLEM BASED LEARNING FOR ARITHMETIC SEQUENCES AND SERIES MATERIAL - Aisyah Rahmawaty; Rani Refianti; Khathibul Umam Zaid Nugroho (Journal of Mathematics Science and Education., 2025)
The purpose of this literature review is to examine and summarize several articles that discuss the development and implementation of Student Worksheets (LKPD) with the Problem Based Learning (PBL) learning model on the Arithmetic Sequences and Series material. The method used in this study is the Systematic Literature Review (SLR) which consists of 6 stages, namely: Research Question, Selection Criteria, Search Strategy, Select Studies, The Quality of Studies, and Synthesis Result. This study uses PICOC analysis (Population, Intervention, Comparison, Outcome, and Context). The articles reviewed amounted to 12 relevant articles and were published from 2020 to 2025. The results of this study indicate that the development and implementation of LKPD have a positive impact on improving student learning outcomes. In addition, the results of this study also show that LKPD using the Problem Based Learning model can hone students' problem-solving skills, mathematical understanding skills, mathematical reasoning and mathematical communication, especially on the Arithmetic Sequences and Series material.